2018
DOI: 10.5430/jbar.v7n1p6
|View full text |Cite
|
Sign up to set email alerts
|

Hedge Strategies of Corporate Houses

Abstract: This paper compares and contrasts the hedge strategies through derivative instruments by Indian and USA corporate houses. The derivative instruments have little predictive power in explaining corporate hedging strategies both in the USA and Indian firms. The purpose of the study is to provide a setting where reconciling conflicting results from the literature may be appropriate and to compare different hedge strategies in a specific period in two different countries (USA and India). The evidence based on multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…To investigate the relationship between the variables of the study, descriptive statistics, two-way ANOVA, and the Levene Test were performed (Ahmadi et al, 2014a;Ahmadi et al, 2014b;Nagahi et al, 2018). Prior to discussing the findings, it is appropriate to discuss the MBTI administration results and present the characteristics of the Iranian EFL learners' sample distribution.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the relationship between the variables of the study, descriptive statistics, two-way ANOVA, and the Levene Test were performed (Ahmadi et al, 2014a;Ahmadi et al, 2014b;Nagahi et al, 2018). Prior to discussing the findings, it is appropriate to discuss the MBTI administration results and present the characteristics of the Iranian EFL learners' sample distribution.…”
Section: Resultsmentioning
confidence: 99%
“…analyzed the factors affecting the behavior of initiating a position in the derivatives market. The study identified the manager's risk attitude, the manager's psychological reference price as the variables in initiating a futures contract Naghai et al (2018). compared the hedging strategies of selected US and Indian companies and found no significant (statistically) variables in explaining the decision to hedge exchange rate risk.…”
mentioning
confidence: 99%